Similaritonic Method on Ultrashort Pulse Duration Measurement by Oscilloscope - M. Sukiasyan; N. P. Karapetyan; H. A. Toneyan; Kutuzyan, A. A.; L. KH. Mouradian
In this work, we developed and experimentally examined a real-time single-shot technique of femtosecond pulse duration measurement based on similariton spectrotemporal imaging and measuring temporal profile via electrical oscilloscope. The method is easy in implementation, since it uses only a piece of single mode fiber and an oscilloscope.
Keywords: Physics; Electronics; radiowave and microwave technology; direct energy conversion and storage